Compliance and Conflict of Value in Public Policy Implementation: Comparison between the New Order and the Reformation Era - Dwiyanto Indiahono; Erwan Purwanto; Agus Pramusinto (Policy & Governance Review, 2018)
This research aims to examine diﬀerences in the relationship of bureaucratic and political oﬃcials during the New Order (Soeharto’s era) and the Reformation (post-Soeharto) era within the arena of public policy implementation. This is a matter of importance given that there is a change in relations between the two from integration in the New Order to bureaucratic impartiality in the Reformation Era. This study attempts to answer the question: How were the relations of bureaucratic and political oﬃcials in the implementation of local level public policy during the New Order and the Reformation Era? A qualitative research has been conducted in Tegal Municipality using the following data collection techniques: interview, focus group discussion, documentation, and observation. Tegal Municipality was selected as the study location because of the unique relationship shown between the mayor and the bureaucracy. Its uniqueness lies in the emergence of bureaucratic oﬃcials who dare to oppose political oﬃcials, based on their convictions that bureaucratic/public values should be maintained even if it means having to be in direct conflict with political oﬃcials. This research indicates that the relationship between bureaucratic and political oﬃcials in the arena of local level policy implementation during the New Order was characterized as being full of pressure and compliance, whereas during the Reformation Era bureaucrats have the audacity to hinder policy implementation. Such audacity to thwart policies is considered to have developed from a stance that aims to protect public budget and values in policies. The occurring conflict of values here demonstrates a dichotomy of political and bureaucratic oﬃcials that is diﬀerent from the prevailing definition of politics-administration dichotomy introduced at the onset of Public Administration studies.